Crizotinib resistance conferred by BRAF V600E mutation in non–small cell lung cancer harboring an oncogenic ROS1 fusion. (2021) - Ren, Shuang; Huang, Sisi; Ye, Xinqing; Feng, Luhuai; Lu, Yang; Zhou, Chaonan; Zhao, Juan; He, Tingting; Wang, Junwei; Li, Bixun
Highlights: Present a case of NSCLC harboring a CD74-ROS1 fusion mutation develop crizotinib resistance with acquired mutation of BRAF V600E. Provide one more clinical evidence on crizotinib resistance mechanism, since there has been only one similar case reported. Provide more insights into patterns of mechanisms of crizotinib resistance in patients with ROS1 -positive cancer are provided. Abstract: Non–small cell lung cancer (NSCLC) patients with oncogenic ROS1 rearrangements would inevitably develop drug resistance and disease progression after receiving targeted oncogene therapy. Here, we present a metastatic lung adenocarcinoma patient harboring a CD74–ROS1 fusion who initially responded to crizotinib and then developed resistance after acquiring a rarely reported BRAF V600E mutation.